PENGARUH CURRENT RATIO, RETURN ON ASSETS RATIO, DAN DEBT TO ASSETS RATIO TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN SEKTOR PROPERTI - ZUCHRUF FIRDAUS; RICHIE DWI FIRMANSYAH (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2021)
The purpose of this research is to examine and and analyze the effect of the Current Ratio (CR), Return on Assets Ratio (ROA), and Debt to Assets Ratio (DAR) on the Dividend Policy (DPR) of property sector companies, which listed in the Indonesian Stock Exchange in the period of 2017-2019. This research is an associative causal research and the type of data used is quantitative data obtained from audited company financial statements in the Indonesian Stock Exchange during the research period. The population of this research are all property sector companies listed in the Indonesian Stock Exchange (IDX). The total population of the company is 70 companies. Based on certain criteria the number of companies that meet the sample criteria are 12 companies. The technique used is multiple linear regression technique. The results of the study simultaneously show the simultaneous effect of the Current Ratio (CR), Return on Assets Ratio (ROA), and Debt to Assets Ratio (DAR) on the Dividend Policy (DPR) of property sector companies listed on the Indonesian Stock Exchange in the period of 2017-2019. The results of the partial test show that the Current Ratio (CR) has a negative and insignificant effect, Return on Assets (ROA) has a positive and significant effect, while the Debt to Assets Ratio (DAR) has no effect on dividend policy (DPR) in property sector companies listed on the Indonesian Stock Exchange in the period of 2017-2019